Studi Kasus: Dinamika Gangguan Psikologis dan Fisik Yang Dialami Pria Pengurus Desa Adat Bali - Kadek Isma Melandari; Taufik Akbar Rizqi Yunanto (Psychocentrum Review, 2022)
Hipertension is dangerous disease that can take the life of the sufferer. Killing sufferers event without symptoms warns everyone to maintain physical health and also mental health. One of the factors that cause hypertension is stress. Including the figures or administrators of the Balinese Traditional Village. The workload is quite heavy and also voluntary (Ngayah) is a source of its own stressor. This Study aims to determine the psychological dynamic that occur in traditional leaders so that it can affected their medical conditions which have an impact on incrasing blood pressure. The method used in the research is case study method with  qualitative approach. The partisipan that involved was one person (N=1). A man 55 years who served as a traditional village leader and carried out duties in village management and suffered high blood pressure. Data was collected by using interview asessment techniques, observation, and also using several psychological instruments to make it easier arrange the psychological dynamic of the participant. The results of this study is the increase of blood pressure experienced by participant is influenced by the presense of strong stressor from dthe social environment.